2023
DOI: 10.1007/s11846-023-00626-z
|View full text |Cite
|
Sign up to set email alerts
|

Institutional and individual determinants of entrepreneurial intentions: evidence from developing and transition economies

Abstract: This study aims to examine the effect of institutions on entrepreneurial intentions, the mediation of individual motives in this relationship, and the moderating effect of the country. We tested a sample of 678 questionnaires using quantitative research methods. We used confirmatory factor, correlation, multiple regression, mediation, and moderated mediation analyses to analyze the data. Findings show that normative institutions affect entrepreneurial intentions in Turkey and Kosovo. They also reveal that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 152 publications
0
5
0
Order By: Relevance
“…We performed an exploratory factor analysis to verify the appropriateness of the data with the subscales used in our research. The results, as shown in Table 2, indicate that the KMO coefficient is 0.874, which signifies that the sample size is suitable for the study (Bağış et al , 2023a; Bağış et al , 2023b; Kryeziu et al , 2022a). The Barlett test of sphericity shows a statistically significant p -value of less than 0.01 ( p = 0.000), further affirming the data’s multiple normal distribution criteria (Bağış et al , 2023b) as validated by the factor loadings.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…We performed an exploratory factor analysis to verify the appropriateness of the data with the subscales used in our research. The results, as shown in Table 2, indicate that the KMO coefficient is 0.874, which signifies that the sample size is suitable for the study (Bağış et al , 2023a; Bağış et al , 2023b; Kryeziu et al , 2022a). The Barlett test of sphericity shows a statistically significant p -value of less than 0.01 ( p = 0.000), further affirming the data’s multiple normal distribution criteria (Bağış et al , 2023b) as validated by the factor loadings.…”
Section: Resultsmentioning
confidence: 88%
“…The final version of our institutional scale comprises seven items, each for the regulatory and normative dimensions and four for the cultural-cognitive dimensions. This scale has been applied in various recent studies (Bağış et al , 2023a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have questioned the relationship between entrepreneurial intentions and behaviors (Liñán et al ., 2011; Arabiyat et al ., 2019). Research shows that the effects of cognitive-cultural institutions on entrepreneurial intentions differ in developing and transition economies (Bağış et al ., 2023a). Similarly, another study conducted in Spain and Taiwan confirmed that culture significantly differentiates entrepreneurial intentions (Liñán and Chen, 2009).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…These studies' limitations in terms of time and variables prompt us to scrutinize this relationship over a more extended timeframe and with a broader set of variables. This endeavor is further supported by recent calls for research and existing studies that advocate institutional explanations for variations in entrepreneurial activity between developed and developing economies (Cao and Shi, 2021; De Mello et al ., 2022; Li et al ., 2021; Sethuram et al ., 2021; Bağış et al ., 2023a).…”
Section: Introductionmentioning
confidence: 99%